Monitoring Mechanism of Formation and Assessment of the Level of Social Policy of the Enterprise - VEDERNIKOV, MYKHAILO; KOSHONKO, HELENA; VOLIANSKA-SAVCHUK, LESIA; ZELENA, MARIA; BAZALIYSKA, NATALIA (The journal of contemporary issues in business and government, 2021)
The article identifies the factors influencing the effectiveness of the formation and implementation of social policy in an industrial enterprise. To this end, the industrial enterprise conducted a corresponding study, according to the results of which 4 criteria characterizing the level of formation and implementation of the social policy of the enterprise were determined and substantiated. The method of rank correlation and the method of expert evaluations were used to process the research results. It is proposed to determine the optimal level of enterprise’s social policy of the using the method of priorities with the ranking of the types of constituent elements according to the selected characteristics. According to the results of this analysis, the scientific assumption about the dependence of the level of the joint venture on the rational use of the constituent elements of this policy is proved.